Proteomic and metabolomic profiling reveals the fungicidal mechanisms of Microsporum canis in response to methylene blue-mediated photodynamic therapy - Peng, Gaoyuan; Qin, Shulei; Xu, Weilun; Cao, Cunwei; Pan, Kaisu; Huang, Lan; Liao, Liuwei; Zhou, Junmeng; Zheng, Dongyan; Zhang, Xinyu (Frontiers in Microbiology, 2026)
BackgroundMicrosporum canis is a primary causative agent of dermatophytosis. Its rising antifungal resistance necessitates the development of effective therapeutic alternatives. Although methylene blue-mediated photodynamic therapy (MB-PDT) is a promising strategy, a system-level understanding of its fungicidal mechanism is lacking.MethodsAn integrated multi-omics approach was employed, using data-independent acquisition (DIA) proteomics and untargeted metabolomics, to map the molecular response of clinical M. canis isolates to MB-PDT. Pathway enrichment analysis was performed to elucidate the key biological processes affected.ResultsMB-PDT induced multi-faceted molecular perturbations in M. canis. The treatment simultaneously disrupted membrane integrity by downregulating ergosterol biosynthesis (e.g., C4-methylsterol oxidase) and impaired the fungus’s antioxidant defenses by suppressing key enzymes such as glutathione S-transferase. Critically, the treatment suppressed secreted virulence factors essential for host invasion, including subtilisin-like protease 7. These disruptions led to a profound suppression of core biosynthetic machinery, with ribosome biogenesis and translation identified as the most significantly inhibited pathways. This resulted in a collapse of protein synthesis, energy production, and amino acid metabolism.ConclusionThe results indicate that the efficacy of MB-PDT stems from a multi-target mechanism that simultaneously damages cellular structures, attenuates virulence, and dismantles the fungus’s metabolic and translational capacity. This contrasts sharply with single-target conventional antifungals, providing a strong molecular rationale for its low potential to induce resistance. This study offers a comprehensive molecular blueprint for the action of MB-PDT against M. canis, strongly supporting its development as a durable therapeutic strategy for dermatophytosis.